Curcumin protects against stroke and increases levels of Notch intracellular domain. (2nd June 2016) - Liu, Shuang; Cao, Yungang; Qu, Man; Zhang, Zheng; Feng, Liang; Ye, Zusen; Xiao, Meijuan; Hou, Sheng T.; Zheng, Rongyuan; Han, Zhao
Abstract : Objectives: To investigate whether curcumin regulates Notch signaling to cause neuroprotection and neurogenesis after focal ischemia reperfusion injury. Method: Focal ischemia reperfusion injury was modeled in rats by occluding the middle cerebral artery. These animals were given either curcumin (300 mg/kg) or corn oil (vehicle) by intraperitoneal injection starting 1 h after stroke and continuing for 7 d. In parallel, sham-operated control animals received vehicle. All animals were killed on day 12. The different treatment groups were compared in terms of neurobehavioral deficits, BrdU incorporation, and levels of doublecortin (DCX) and Notch intracellular domain (NICD) using immunohistochemistry, immunofluorescence and Western blotting. Results: Animals treated with curcumin showed significantly smaller neurobehavioral deficits than vehicle-treated animals after 3, 7, and 12 d of reperfusion (all p < 0.05). Tissue sections from curcumin-treated animals contained significantly greater numbers of BrdU-positive cells ( p < 0.05) and BrdU/DCX-positive cells ( p < 0.01), as well as significantly higher NICD levels ( p < 0.01). Conclusion: Curcumin may protect from focal cerebral ischemia reperfusion injury as well as stimulate neurogenesis by activating the Notch signaling pathway.